Analysis of Opportunities and Challenges for Design Consultants and Contractors in Building Projects Using the Design-Build Delivery System - Nabila Ardianty; Naura Dwifarasti; Iris Mahani (Jurnal Teknik Sipil, 2026)
The Design-Bid-Build (DBB) method remains entrenched in Indonesia's construction sector, despite recognized inefficiencies regarding project duration and coordination. The Design-Build (DB) method, offering enhanced integration by combining design and construction responsibilities within a single entity (the designbuilder), has emerged as a significant alternative. Although DB presents advantages, its implementation poses distinct challenges for both design consultants and contractors. This study aims to empirically identify the key opportunities and challenges encountered by design consultants and contractors participating in building projects utilizing the DB method in Indonesia. Employing a mixed-methods approach, quantitative data were gathered via questionnaires and analyzed using the Relative Importance Index (RII), while qualitative insights were obtained through interviews and subjected to descriptive analysis. The research focused specifically on design consultants and contractors involved in Indonesian DB building projects, yielding 8 consultant and 20 contractor respondents. Findings indicate that the primary opportunity for both parties stems from early and sustained collaboration inherent in the DB model, facilitating streamlined project execution. However, significant challenges persist that design consultants face, including compressed timelines for preparing bidding documentation and finalizing designs, while contractors encounter difficulties in securing timely design approvals and exercising adequate on-site project control. This research provides crucial empirical evidence on the specific dynamics affecting key stakeholders, contributing valuable insights for optimizing the implementation of the Design-Build procurement system within the Indonesian construction industry.